Prevalence of Parasites in Soil by two Floatation Techniques and Modified Acid-Fast stain in Baghdad city (Journal of the College of Basic Education, 2023)
The objective of the present study is to determine the prevalence ofparasitic forms such as (eggs, Oocysts,....etc) in soil texture (loam) duringthe period from September 2013 to March 2014 by using two floatationtechniques (Saturated salt floatation and Sheather’s floatation techniques),in addition to the Modified acid fast stain technique to detect Oocyst. 100soil samples were collected from different locations and random areas in(50 soil samples from Al-Karch & 50 soil samples from Al-Rusafa) forisolation the parasites by two floatation techniques, and modified acid faststain method in Baghdad city. Our result showed that, Toxocara spp. eggsisolated by two floatation techniques in (48.00%&42.00%) from Al-Karch& Al-Rusafa places respectively, in addition to the Chi-Square appearedhighly significant for this isolation (9.25)(